Diagnostic Accuracy of a Host Gene Expression Signature That Discriminates Clinical Severe Sepsis Syndrome and Infection-Negative Systemic Inflammation Among Critically Ill Children. Issue 4 (April 2017) - Zimmerman, Jerry J.; Sullivan, Erin; Yager, Thomas D.; Cheng, Catherine; Permut, Lester; Cermelli, Silvia; McHugh, Leo; Sampson, Dayle; Seldon, Therese; Brandon, Richard B.; Brandon, Roslyn A.
Abstract : Objectives: SeptiCyte Lab (Immunexpress, Seattle, WA), a molecular signature measuring the relative expression levels of four host messenger RNAs, was developed to discriminate critically ill adults with infection-positive versus infection-negative systemic inflammation. The objective was to assess the performance of Septicyte Lab in critically ill pediatric patients. Design: Prospective observational study. Setting: Pediatric and Cardiac ICUs, Seattle Children's Hospital, Seattle, WA. Patients: A cohort of 40 children with clinically overt severe sepsis syndrome and 30 children immediately postcardiopulmonary bypass surgery was recruited. The clinically overt severe sepsis syndrome children had confirmed or highly suspected infection (microbial culture orders, antimicrobial prescription), two or more systemic inflammatory response syndrome criteria (including temperature and leukocyte criteria), and at least cardiovascular ± pulmonary organ dysfunction. Interventions: None (observational study only). Measurements and Main Results: Next-generation RNA sequencing was conducted on PAXgene blood RNA samples, successfully for 35 of 40 (87.5%) of the clinically overt severe sepsis syndrome patients and 29 of 30 (96.7%) of the postcardiopulmonary bypass patients. Forty patient samples (~ 60% of cohort) were reanalyzed by reverse transcription-quantitative polymerase chain reaction, to check for concordance with next-generation sequencing results. Postcardiopulmonary bypass versus clinically overt severe sepsis syndrome descriptors included the following: age, 7.3 ± 5.5 versus 9.0 ± 6.6 years; gender, 41% versus 49% male; Pediatric Risk of Mortality, version III, 7.0 ± 4.6 versus 8.7 ± 6.4; Pediatric Logistic Organ Dysfunction, version II, 5.1 ± 2.2 versus 4.8 ± 2.8. SeptiCyte Lab strongly differentiated postcardiopulmonary bypass and clinically overt severe sepsis syndrome patients by receiver operating characteristic curve analysis, with an area-under-curve value of 0.99 (95% CI, 0.96–1.00). Equivalent performance was found using reverse transcription-quantitative polymerase chain reaction. There was no significant correlation between the score produced by the SeptiCyte Lab test and measures of illness severity, immune compromise, or microbial culture status. Conclusions: SeptiCyte Lab is able to discriminate clearly between clinically well-defined and homogeneous postcardiopulmonary bypass and clinically overt severe sepsis syndrome groups in children. A broader investigation among children with more heterogeneous inflammation-associated diagnoses and care settings is warranted. Abstract : Supplemental Digital Content is available in the text.